Skilled labour shortage: a qualitative study of Ghana’s training and apprenticeship system - Dayaram, Kandy; Ayentimi, Desmond; Burgess, J. (Routledge, 2018)
The impacts of training and apprenticeship education towards building high-level technical and vocational skills that support human capital development and attracting foreign direct investment are being reshaped by global competition. This article draws on human capital theory to report on a qualitative study that explores skilled labour challenges within Ghana’s training and apprenticeship system through the lens of the demand side of employment perspective. The findings point to a training mismatch, lack of regulations and ineffective apprenticeship programmes, underinvestment in education and training, and outdated training programmes. The bottlenecks in the supply of skilled labour in Ghana are hampering the firms’ ability to find skilled labour across industries. We suggest improved social partnership between industries and training institutions, with increased government investment in training and apprenticeship programmes, as a way forward to address the technical and vocational skilled labour supply bottlenecks. Wider implications for the African region which shares similar developing contexts are discussed.